APPLICATION OF THE DISCOVERY LEARNING MODEL TO IMPROVE MATHEMATICS LEARNING OUTCOMES OF CLASS XI MIA 1 BABUSSALAM SENIOR HIGH SCHOOL PEKANBARU - Silvi Nanda; Armis (Jurnal Prinsip Pendidikan Matematika, 2022)
The purpose of this study is to improve the mathematics learning process and student performance by applying the Discovery learning model. is composed. This exploration is an excellent case study with two rounds. The tools for this study are instructional tools (syllabus, Lesson Plans, and worksheets), data collection tools (teacher and student observation sheets), and student math tests. The data collection methods of this study are the observation method and test method. The observation papers were analyzed in the descriptive type, and the students' math test was analyzed in the statistical narrative type. The data analysis of this study is the analysis of observation data of teachers and students and the analysis of student learning performance data in mathematics. The teacher and student observation data analysis revealed that the curriculum improved after completing the behaviour (first and second cycle). Research of data about student performance shows that student performance has improved in math. The number of students in the "very high" and "high" ranges increases. On the other hand, the number of students in the “very low”, “low” and “medium” segments is declining. Based on the results of this study, it can be concluded that the implementation of the Discovery learning model can improve the mathematics curriculum and student performance in the XI MIA 1 SMA Babussalam Pekanbaru classroom.